ANALISIS KETIMPANGAN PENDAPATAN DAN PENGEMBANGAN SEKTOR UNGGULAN DI KABUPATEN DALAM KAWASAN BARLINGMASCAKEB TAHUN 2007-2010 - Adi Sutrisno Sutrisno (Economics Development Analysis Journal, 2012)
This study aims to analyze the magnitude of income disparities among districts in the region Banjarnegara,Purbalingga, Banyumas, Cilacap, Kebumen (Barlingmascakeb) and identify sectors that can be developed in each district who are members of the Barlingmascakeb. The data used in this study is secondary data while the method for collecting data use the documentation method. The analytical methodused the analysis of Williamson’s index, Theil entropy index, location quotient, shift share, typology Klassen, skalogram. The results show that thre are imbalace income in the region Barlingmascakeb of the Year 2007-2010 by an average of 0.185 (Williamson index) and 0.722 (Theil entropy index). These results suggest that imbalace income in the region is relatively still low Barlingmascakeb. Banjarnegara has a dominant sector in the services sector. Purbalingga have sectors in construction, trade, finance and services. Banyumas has a dominant sector in the building sector, financial services and clean water gas electricity. Cilacap has a dominant sector in agriculture, trade and processing industry. Kebumen has a dominant sector in the agriculture, mining and quarrying. Cilacap and Banyumas district includes the counties with complete infrastructure.